Interaction of herbs and tree saplings is mediated by soil fertility and stand evergreenness in southern Appalachian forests. (27th November 2019) - Gafta, Dan; Peet, Robert K.
Abstract: Aims: Competitive inhibition of temperate forest tree recruits by herbs is likely important on sites with high fertility owing to faster height growth and consequent pre‐emption of light. We explored the site conditions and stand structure under which herbaceous growth has an impact on tree regeneration. Location: Plot data from 610 forest sites were collected from five areas across the southern Appalachian Mountains. Methods: Several plant guilds were distinguished based on various biological traits. Deterministic models of forest understorey were validated through recursive path analysis. The numerical analyses were performed both on all plots and on a subset of 150 plots free of evergreen shrubs. Results: In general, total herb cover increased with soil fertility, but in sites without evergreen shrubs no relationship emerged. Total herb cover varied inversely with woody stem density (saplings excluded), but the slope was much less steep in the absence of evergreen shrubs. Tree sapling density displayed a left‐tailed, asymmetric response with respect to total herb cover, but a symmetric unimodal response against tall herb cover. The shape of the distribution of tree stems by diameter class shifted from unimodal under a very sparse herbaceous layer to negative exponential in stands with mid to high herb cover. This was due to the suppressive impact of evergreen shrubs on understorey vegetation, which led to a positive covariance between total herb cover and tree sapling density. These two understorey variables became unrelated in the path model built on the subset without evergreen shrubs, but a similar model involving tall herbs revealed a direct negative effect of tall herb cover on tree sapling density. Conclusions: Our results provide evidence of tree recruits exclusion by tall herbs on fertile sites but not on acidic sites, where herb interference is much reduced by the suppressive effect of evergreen shrubs and trees on herbaceous layer vegetation. Abstract : The interaction between herbs and tree recruits in southern Appalachian forests can range from positive covariance under the suppressive effect of evergreen shrubs in sites with acidic soils, to competitive exclusion of small tree saplings through interference from tall herbs in base cation‐rich sites.